'APPLICATION OF RESTORATIVE JUSTICE IN THE INVESTIGATION OF NARCOTICS CRIMES ACCORDING TO POSITIVE LAW AND ISLAMIC LAW (STUDY ON THE JURISDICTION OF THE INDONESIAN NATIONAL POLICE SOUTH BORNEO REGION) - Siswoyo, Siswoyo; Jamalie, H. Zulfa; Mujiburrohman, Mujiburrohman (Proceeding International Seminar of Islamic Studies, 2024)
Restorative Justice is a new concept of thinking that develops as a response to the retributive justice system and criminal justice that is considered unsatisfactory to the sense of justice of the community. The problem arises when drug crimes that are considered victimless crimes cannot be applied restorative justice in them because there are no victims, on the contrary, according to other legal experts, they argue that drug abusers themselves are perpetrators and victims. On the above issues, research has been conducted to find out how South Kalimantan police investigators, especially the Ditresobat, apply restorative justice in investigations Drug crimes, what are the obstacles faced and what is the perspective of Islamic law and positive law in applying ideal restorative justice in drug investigations? This research uses a socio-legal approach combination of document studies and field studies. The source of the data was obtained from interviews with five informants (four from the South Kalimantan Regional Police and 1 informant from the South Kalimantan BNNP). Primary legal materials used by all regulations related to restorative justice in the investigation process and case studies of investigations (using 6 case studies) of drug crimes in the South Kalimantan regional police area. Based on Pustaka searches and interview results, the application of restorative justice in the investigation of narcotics crimes by Investigators in the jurisdiction of the Indonesian National Police in the South Kalimantan Region has been running in accordance with applicable procedures but still gets obstacles derived from its own legal factors, law enforcement factors, facilities or facilities factors, and community factors. In the perspective of national law, normative references to restorative justice in drug crimes have not been comprehensive, so state consistency through law enforcement officials is needed in implementing different treatment between drug users and dealers. Meanwhile, in the perspective of Islamic law, victims of drug abuse who undergo rehabilitation do not deviate from Islamic criminal law because the purpose of jarimah ta'zir in addition to providing a deterrent effect to the person concerned also has a positive impact after the law is implemented, namely the safety of body and soul as the main purpose, vision and mission of the Ditresobat Polda South Kalimantan. Based on the results of the study, the researcher reconstructed 3 steps that must be taken by investigators in the jurisdiction of the Indonesian National Police in South Kalimantan Region in implementing restorative justice for drug convicts, namely by increasing the progress of investigators in law enforcement against drug addicts, synergy of assessment teams towards users and socialization of medical rehabilitation priorities over legal rehabilitation.